2012
DOI: 10.1159/000335830
|View full text |Cite
|
Sign up to set email alerts
|

Eleven Years’ Experience with Korean Cardiac Myxoma Patients: Focus on Embolic Complications

Abstract: Background: Cardiac myxomas are rare but are the most common cardiac tumors. This study is based on our clinical experience with cardiac myxomas over a period of 11 years at Sejong General Hospital. We focused on the embolic complications of patients with cardiac myxoma. Methods: We retrospectively reviewed the medical records of 59 consecutive patients with cardiac myxoma who were treated between January 2000 and March 2011. The myxomas were divided into two types: type 1, with an irregular or villous surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
98
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 54 publications
(65 reference statements)
3
98
1
3
Order By: Relevance
“…Asymptomatic ventricular dysfunction has also been associated with elevated natriuretic peptides [29]. It should also be acknowledged that there could be other links between natriuretic peptides and cardioembolic stroke, such as hypertension, valvular disease, cardiac myxomas, and recent coronary events [2,23,30]. In addition, renal dysfunction can increase levels of natriuretic peptides [31].…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic ventricular dysfunction has also been associated with elevated natriuretic peptides [29]. It should also be acknowledged that there could be other links between natriuretic peptides and cardioembolic stroke, such as hypertension, valvular disease, cardiac myxomas, and recent coronary events [2,23,30]. In addition, renal dysfunction can increase levels of natriuretic peptides [31].…”
Section: Discussionmentioning
confidence: 99%
“…The size of the atrial myxoma is variable with a mean of 2.7 (range, 0.4-6.5) cm as reported by Lee et al [2], and was 4.8±1.9 cm by Lee et al [11]. Neurologic complications of atrial myxoma are most frequently cerebral infarcts caused by detached thrombus from the myxoma; while rarely by tumor fragments [2].…”
Section: Discussionmentioning
confidence: 90%
“…Alvarez-Sabín et al [10] reported 11 of 28 (39.3%) cardiac myxoma patients had embolic phenomena, which affected the cerebral arteries in 6 (54.5%), peripheral arteries in two (18.2%) and both cerebral and peripheral arteries in three (27.3%) patients. Lee et al [11] reported 13 of 59 (22.0%) patients with a cardiac myxoma developed embolic events, 11 (18.6%) of which were in the brain, Two (3.4%) in the limb and one (1.7%) in the eye. Furthermore, Yuan [12] reported a patient with a delayed cardiac myxoma resection developed multiple embolic events in the lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“…In majority of cases the cerebral arteries are affected leading to ischemic stroke. [5][6][7][8] Stroke, associated with myxomas is usually caused by embolisation of tumor or thrombus and classically involves several vascular territories. However, aneurysm formation and intacerebral or subarachnoid hemorrhage have been reported.…”
Section: Discussionmentioning
confidence: 99%